Facile synthesis of porous Ag3PO4 photocatalysts with high self-stability and activity. Issue 61 (13th June 2016) - Yu, Hongchao; Jiao, Zhengbo; Jin, Bingjun; Feng, Chenchen; Lu, Gongxuan; Bi, Yingpu
Abstract : 1D Ag3 PO4 hollow porous microrods have been fabricated with Ag2 WO4 as growth templates, which exhibit enhanced photocatalytic activity and stability for the degradation of organic contaminations compared with Ag3 PO4 cubes and particles. Abstract : One-dimensional (1D) Ag3 PO4 hollow porous microrods have been fabricated for the first time by using Ag2 WO4 microrods as the Ag + ion source and growth template, which exhibit substantively enhanced photocatalytic activity and stability for the degradation of organic contaminations compared with Ag3 PO4 cubes and particles under visible light irradiation.